THE SURVIVING OF THE SIGNS, THE INVOLUNTARY MEMORY OF THE STRANGER AND THE URBAN SPACE IN RUINS: THE REPRESENTATIONS OF THE SIGNS OF MUNDANITY, LOVE, SENSITIVE QUALITIES AND ART IN MILTON HATOUM - Ferreira, Cacio José; Júnior, Norival Bottos (fólio - revista de letras, 2019)
This article has the intention to understand some qualities and pluralities of signs issued on the three first novels of Milton Hatoum, Relato de um certo Oriente (2014), Dois irmãos, (2007), Órfãos do eldorado, (2008), Cinzas do Norte. (2012). Departing from the theorical assumptions by Gilles Deleuze and Félix Guattari about the way of interpretation of the memories signs: like the signs of love, sensibilities, mundanities and art, this last is responsible for gathering the other forms of art. The goal is try to become evidente how the modulations of intensitie´s productions and individuation not segmented in binarysm give the chance to understand that in Milton Hatoum`s Works the theme is not the memory, but the surviving of traumatic images, the symptons of violence, the ghosts and the surviving of the signs. The signs of love, for example, besides the fact that they are conected to the signs of art, they give us the chance to undestand how survive incestuous forms of love, recurrent theme in Milton Hatoum. Finally, these new forms of individuation and production of subjectivity that not return is a complex game of ruins on the form of memories, but, in the words of Gilles Deleuze, in practices of production of signs that affect and let to be affect for others plural subjectivities. The result is the fact that the capture of these signs in Milton Hatoum`s novels has not the power to go beyond of what immersed in the signs repeat, repelling and dialogues between themselves.